Dampak Alih Fungsi Lahan Pertanian Menjadi Area Industri Peternakan Ayam (Study Kasus Kondisi Sosial Ekonomi Masyarakat Desa Terentang Kecamatan Banyuasin III Kabupaten Banyuasin) - Pusnita, Indah; Novianti, Rahmi; Mahdiana, Yana; Muslimaini, Heni (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2022)
This research aims to determine the impact of the change of function on agricultural land which is currently an area for the chicken farming industry in Terentang Village, Banyuasin Regency. This research uses a qualitative research method approach with data collection techniques in the form of observation, interviews and documentation. Data is in the form of information collected through interviews conducted with informants. Data analysis goes through several stages, namely data reduction, data display and drawing conclusions. The results of the research show that the impact of changing the function of agricultural land into a chicken farming industrial area, case study, socio-economic conditions of village communities is broad, namely measured based on economic, social and ecological impacts. The economic impact is measured based on production costs and production prices which have a positive impact on the community and chicken farming business owners so that it can create prosperity for rural communities; Social Impact on the community has a negative impact, namely the smell of chicken droppings which disrupts community activities, which will have an impact on the health of the local community; Then the ecological impact is making existing land used as a chicken farming area making it difficult to use for farming, this of course requires quite a long time to restore the soil's fertility. The conversion of agricultural land into chicken farming industrial areas has had quite a significant impact, starting from the socio-economic aspects of the community in the village, which has improved so that prosperity can be created for the community, compared to before the conversion of land, which had caused the economic condition of the community to drop drastically with the price of rubber which is low, and different when the land function is changed, the economic condition of the community improves again.